MICROSTRUCTURE AND MARTENSITIC TRANSFORMATION OF Ni_50Ti_50-xEr_x SHAPE MEMORY ALLOYS - Dovchinvanchig, M.; Gangantogos, Ya.; Munkhjargal, B. (Mongolian Journal of Engineering and Applied Sciences, 2021)
The effect of rare earth element Er addition on the microstructure and phase transformation behavior of Ni_50Ti_50-xEr_x (x =0, 1, 5) shape memory alloy was investigated experimentally. The results showed that the microstructure of Ni-Ti-Er ternary alloys consists of the NiEr precipitate and the NiTi matrix. A one-step martensitic transformation was observed in all alloys. The martensitic transformation temperature M_s increased gradually with increasing Er content.